CRYSTALLOCHEMICAL CHARACTERIZATION OF THE PALYGORSKITE AND SEPIOLITE FROM THE ALLOU KAGNE DEPOSIT, SENEGAL - García-Romero E.; Suárez M.; Santarén J.; Alvarez A. (My University, 2007)
The Allou Kagne (Senegal) deposit consists of different proportions of palygorskite and sepiolite, and these are associated with small quantities of quartz and X-ray amorphous silica as impurities. No pure palygorskite or sepiolite has been recognized by X-ray diffraction. Textural and microtextural features indicate that fibrous clay minerals of the Allou Kagne deposit were formed by direct precipitation from solution. Crystal-chemistry data obtained by analytical/transmission electron microscopy (AEM/TEM) analyses of isolated fibers show that the chemical composition of the particles varies over a wide range, from a composition corresponding to palygorskite to a composition intermediate between that of sepiolite and palygorskite, but particles with a composition corresponding to sepiolite have not been found. Taking into account the results from selected area electron diffraction and AEM-TEM, fibers of pure palygorskite and sepiolite have been found but it cannot be confirmed that all of the particles analyzed correspond to pure palygorskite or pure sepiolite because both minerals can occur together at the crystallite scale. In addition, the presence of Mg-rich palygorskite and very Al-rich sepiolite can be deduced. It is infrequent in nature that palygorskite and sepiolite appear together because the conditions for simultaneous formation of the two minerals are very restricted. The chemical composition of the solution controls the formation of the Allou Kagne sepiolite and palygorskite. The wide compositional variation appears as a consequence of temporary variations of the chemical composition of the solution.
Keywords: AEM-TEM; ALLOU-KAGNE DEPOSITS; CRYSTAL CHEMISTRY; PALYGORSKITE; SAED; SENEGAL; SEPIOLITE